Side-channel photonic crystal fiber for optofluidic sensing - Wu, Liuyi (2017)
In the project, an in-line interferometer using side-channel photonic crystal fiber (SCPCF) was proposed and experimentally demonstrated for temperature detection and refractive index sensing. The SCPCF was designed that supported a solid core bounded by a large amount of air holes in the cladding as well as a large flabellate side channel which could be filled with liquid. It could also support the modified total internal reflection mechanism for light propagation. Then, an in-line SMF-SCPCF-SMF was built via splicing single mode fibers at both terminals of SCPCF and it supported 01 mode and 11 mode in the core and cladding of SCPCF respectively. The transmission spectrum with a wavelength range from 1450nm to 1650nm was analyzed by an optical spectrum analyzer. The experimental results indicated that the transmission attenuation was 1.527dB/m, which was mainly caused by MFD mismatching and coupling loss. With the temperature increased from 30°C to 70°C with a step of 5°C, the temperature sensitivity was calculated as 0.0061nm/℃ by exploring the shift of dip wavelength. After that, the effective refractive indexes of 01 mode and 11 mode were simulated at specific wavelengths and temperature by COMSOL. Combining the temperature sensitivity and the variation of effective refractive indexes of 11 mode, the refractive index sensitivity was derived as high as 5323.42nm/RIU. Considering the acceptable value of transmission loss, temperature sensitivity and refractive index sensitivity, this SMF-SCPCF-SMF interferometer will have great application prospects for temperature and refractive index sensing. Key words: SCPCF, interferometer, temperature sensitivity, refractive index sensitivity